Long-term monitoring of temperate macroalgal assemblages inside and outside a No take marine reserve. (January 2020) - Medrano, Alba; Linares, Cristina; Aspillaga, Eneko; Capdevila, Pol; Montero-Serra, Ignasi; Pagès-Escolà, Marta; Zabala, Mikel; Hereu, Bernat
Abstract: Macroalgal communities have an essential role in the shallow benthic habitats of temperate seas, where changes in their composition can resonate through entire coastal ecosystems. As all major ecosystems on Earth, algal beds have already been affected by multiple disturbances. Passive conservation tools, such as marine protected areas or No-take zones, have the potential to reduce some of the anthropogenic impacts by limiting human activity. However, without a good knowledge of the natural community dynamics, it is not easy to discern between changes fruit of the intrinsic variability of biological communities and the ones caused by human-related stressors. In this study, we evaluated the natural variability of macroalgal communities' composition inside and outside a Mediterranean No-Take marine reserve during 15 years. We described their temporal dynamics considering their main drivers and we tested the effect of protection in seaweed beds. We did not find differences either in the composition of the macroalgal assemblages or the total algal cover between protected and non-protected locations over the fifteen years of study. Nevertheless, we observed a positive effect of the protection increasing the cover of some specific species, such as the canopy-forming Treptacantha elegans . Our results highlight the importance of obtaining long-term data in ecological studies to better understand the natural variability of marine communities. Accordingly, a robust understanding of the community dynamics would help us to avoid misinterpretations between 'impacted' or 'in-recovery' communities when recovery times are longer than the study periods. Highlights: Long-term stability of macroalgal assemblages. Marine protection does not affect the most representative macroalgal species. Long-term monitoring is key for a better understanding of the natural dynamics of benthic populations. A current and unique baseline of the rocky-shallow infralittoral macroalgal assemblages in the NW Mediterranean Sea.